Efeito de Calotropis procera no controle de Meloidogyne incognita e aspectos biológicos do nematioide em tomateiro - Costa, Natalia de Jesus Ferreira (2017)
The root-knot nematodes, belonging to the genus Meloidogyne, constitute the one of the most important group of nematodes in agriculture. The search for methods of control of these phytopathogens, without the use of nematicides, has induced ways to manage these pathogens using vegetal extracts. The objectives of the current study were to to investigate the potential of use leaves of Calotropis procera in the control of M. incognita race 2 in tomato (Solanum lycopersicum) cv. Carolina and to study biological aspects of the phytonematoid by means of six assays: (1) to evaluate the susceptibility of C. procera to M. incognita; (2) to verify the in vitro effect of aqueous extracts of C. procera leaves at 5 and 10% on the hatching of juveniles of M. incognita; (3) to investigate the in vitro effect of 5 and 10% C. procera leaves aqueous extracts on the mortality of second stage juveniles (J2) considering the length of time (24 and 48 hours) of the J2 in the extract and the time of storage of the leaves used in the preparation of the extract (1 day and 62 days after drying the leaves); (4) to evaluate the application of the aqueous extract of leaves 5 and 10% of C. procera by irrigation in soil infested with M. incognita; (5) to investigate the effect of the incorporation of fresh leaves of C. procera in soil infested with M. (6) to evaluate the population of males in comparison to the population of females and the number of eggs of M. incognita in tomato roots at 30, 60, 90 and 120 days after inoculation.Were evaluated:weight fresh of shoot (WFS), dry weight of shoot (DWS), plant height (PH), fresh weight of root (FWR), galls numbers (GN), egg masses numbers (EMN), eggs numbers ( EN), gall index (GI), egg masses index (EMI), reproduction factor (RF), reduction in the reproduction factor (RFR), parasitism reduction (PR), number of males (NM) and number of females (NF). The experimental design was the completely randomized design, with 7 to 10 replicates, according to the assay and the results of the variables analyzed by the Tukey test at 5%.Based on GI (3.8), EMI (3.0) and RF (0.52) obtained, C. procera was considered resistant to the pathogen.The in vitro test results demonstrated that the 10% aqueous extract caused the greatest inhibition of hatching of the juveniles of M. incognita, with an average of only 13.2% of juvenile hatched was recorded. This same dilution caused the mortality of 92.2% of the J2 after stay for 24h in the extract, being considered the best combination of dilution and time. The extract prepared with leaves stored for 1 day after drying caused 92.7% killing of juveniles. However, the extract obtained from leaves stored at 62 days, the J2 mortality percentage was 11.0%.The application of the aqueous extract to the infested soil was effective in reducing the nematodes parasitism in tomato, with a PR of 80.05 and 78.14% with extracts at 5 and 10%, respectively.The incorporation of both doses (50 and 100 g) of fresh leaves of C. procera promoted the eradication of M. incognita from soil.Males were observed only 60 days after inoculation. The NF:NM relation was 2:1 at 60 days, 3:1 at 90 days and 1.4:1 at 120 days, and the highest average NM (770 males/root) was observed at 90 days after inoculation, at which time an average of 88,956 eggs/root were recorded. The use of aqueous extracts and the incorporation of C. procera leaves are promising alternatives for the control of M. incognita race 2 in infested soil and despite being considered rare, males were abundant in roots of tomato plants cv. Carolina.